2011
DOI: 10.3109/08880018.2010.535118
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopathy-thrombocytopenia Syndrome (HTS) after Actinomycin-D Therapy: Report of Three Cases and Review of the Literature

Abstract: Hepatopathy-thrombocytopenia syndrome (HTS) is a severe complication very similar to vein occlusive disease (VOD), also known as hepatic sinusoidal obstructive syndrome (SOS), characterized by fever, hepatopathy (hepatomegaly with abnormal liver function tests), ascites, weight gain, jaundice, and thrombocytopenia (platelet count less than 25 × 10(3)/μL). It has been generally observed in patients with Wilms tumor, and is commonly associated to administration of actinomycin D. We report three children with Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…In one case series of Wilms tumor, isolated severe thrombocytopenia was the most striking earliest sign with a median platelet count of 12 × 10 9 /l (range 4–48 × 10 9 /l) before signs of HSOS became evident . Others have also reported this observation in patients with Wilms tumor and proposed naming it “hepatopathy‐thrombocytopenia syndrome.” The authors concluded that children developing “isolated” thrombocytopenia following actinomycin‐D are “at risk” of developing HSOS, which, given the liver biopsy findings, is unlikely to be related to the immune‐mediated effect of actinomycin‐D . In another study, 12% of patients with ALL had severe persistent thrombocytopenia out of proportion with the degree of neutropenia and thought to be the sentinel clue for 6‐thioguanine induced HSOS .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In one case series of Wilms tumor, isolated severe thrombocytopenia was the most striking earliest sign with a median platelet count of 12 × 10 9 /l (range 4–48 × 10 9 /l) before signs of HSOS became evident . Others have also reported this observation in patients with Wilms tumor and proposed naming it “hepatopathy‐thrombocytopenia syndrome.” The authors concluded that children developing “isolated” thrombocytopenia following actinomycin‐D are “at risk” of developing HSOS, which, given the liver biopsy findings, is unlikely to be related to the immune‐mediated effect of actinomycin‐D . In another study, 12% of patients with ALL had severe persistent thrombocytopenia out of proportion with the degree of neutropenia and thought to be the sentinel clue for 6‐thioguanine induced HSOS .…”
Section: Discussionmentioning
confidence: 99%
“…Wilms tumor and proposed naming it "hepatopathy-thrombocytopenia syndrome." 1,2 The authors concluded that children developing "isolated" thrombocytopenia following actinomycin-D are "at risk" of developing HSOS, which, given the liver biopsy findings, is unlikely to be related to the immune-mediated effect of actinomycin-D. 19 In another study, 12% of patients with ALL had severe persistent thrombocytopenia out of proportion with the degree of neutropenia and thought to be the sentinel clue for 6-thioguanine induced HSOS. 4 The current understanding of HSOS pathophysiology emphasizes that consumptive thrombocytopenia and refractoriness to platelet transfusions secondary to uncontrolled endothelial/sinusoidal activation is the hallmark of HSOS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, several studies confirm that cisplatin and another alkylating agent such as carboplatin have been rarely associated with the development of veno-occlusive disease in patients who had undergone stem cell transplantation [15]. This is not really true for actinomycin-D that has been associated to veno-occlusive disease and SOS in children [16], and that was administered to our two patients with hepatic sarcoma. But even in those patients, we did not find any CALI.…”
Section: Discussionmentioning
confidence: 75%